(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Wireless Sensor Networks (WSN) are becoming more and more popular everyday due to their increasing ability to monitor certain phenomenon over wide regions such as air pollution, natural disaster, industrial monitoring and underwater applications [1]. The simple security capabilities of the nodes in the sensors network makes it an easy target for an intruder to take over some of the node(s) in the sensor network and to start altering the data received or sent by these nodes before forwarding it to the other nodes in effort to prevent the destination from properly decoding or reading the received data. These attacked nodes lead to tremendous amount of unusable data travelling across the network. The objective of this paper aims to detect these malicious nodes and cast them outside the network using a cooperative local voting approach with a dynamic center and study its effect on the amount of aggregated data though the network and the time required to deliver the sensors data.